Tudor Domain Containing Protein 3 Promotes Tumorigenesis and Invasive Capacity of Breast Cancer Cells - Alan Morettin; Geneviève Paris; Younes Bouzid; R. Mitchell Baldwin; Theresa J. Falls; John C. Bell; Jocelyn Côté (Scientific Reports, 2017)
Abstract Tudor domain containing protein 3 (TDRD3) is a modular protein identified based on its ability to recognize methylated arginine motifs through its Tudor domain. We have previously shown that TDRD3 localizes to cytoplasmic stress granules, a structure shown to promote survival upon treatment with chemotherapeutic drugs in cancer cells. Here, we report TDRD3 as a novel regulator of cell proliferation and invasion in breast cancer cells. Our study also demonstrates that TDRD3 depletion inhibits tumor formation and metastasis to the lung in vivo. Furthermore, we show that TDRD3 regulates the expression of a number of key genes associated with promotion of breast cancer tumorigenesis and disease progression. Strikingly, we report that TDRD3 regulates some of these key targets at the level of translation. These findings provide the first experimental demonstration of a functional role for TDRD3 in promoting breast cancer development and progression, and identify TDRD3 as a potential new therapeutic target for breast cancer.